Real estate application and recommendation system development (I) - Lim, Jensen Chang Sheng (Nanyang Technological University, 2024)
The selection of an appropriate property for purchase is a complex task that necessitates not only a comprehensive understanding of the intricate real estate market but also the ability to comprehend and evaluate various decision-making factors. In response to these challenges, and to demonstrate the potential of technology in enhancing the real estate sector, a cross-platform application, SingaporeOnLine, has been proposed for development. This application is designed to offer a state-of-the-art recommendation system, with a focus on user interaction to ensure customer retention for PropNex clients. Moreover, the designed recommendation system incorporates proven methodologies, along with enhancements to these approaches. The frontend of this application is developed using the Ionic-Angular framework and this cross-platform solution supports both web and mobile platforms, making it highly versatile and capable of catering to PropNex’s extensive and diverse client base. The backend of the application is powered by the Firebase Realtime Database. This robust and scalable database solution houses all PropNex listings, which have been provided directly by PropNex, ensuring that our application has access to the most accurate and up-to-date property information. This comprehensive approach to application design and development underscores the development team’s commitment to enhancing the property buying experience through the innovative use of technology.